2015
DOI: 10.1039/c4ra17090c
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-free heteropolyacid-catalyzed glycerol ketalization at room temperature

Abstract: Currently, the glycerol has been produced in large amounts as biodiesel co-product. Therefore, to develop processes to convert it to more valuable chemicals has attracted significance attention. Glycerol ketals are compounds useful as synthesis intermediates, and fragrances ingredient and mainly, bioadditives for diesel and gasoline, and have been produced trough reactions catalyzed by mineral acids. In this work, we assessed the activity of H 3 PW 12 O 40 heteropolyacid on glycerol ketalization with different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 37 publications
0
37
0
Order By: Relevance
“…da Silva et al ( 2015b ) evaluated the activity of various Brønsted acid catalysts e.g., HPW, H 2 SO 4 , p-toluene sulfonic acid, PMo, or SiW on glycerol ketalization with different ketones (e.g., propanone, butanone, cyclopentanone, and cyclohexanone) at room temperature and in the absence of an auxiliary solvent. The HPW sample exhibited the highest activity among the Brønsted acid catalysts and exhibited high (> 85%) selectivity toward five-membered (solketal) cyclic ketals.…”
Section: Catalytic Acetalization Of Glycerolmentioning
confidence: 99%
“…da Silva et al ( 2015b ) evaluated the activity of various Brønsted acid catalysts e.g., HPW, H 2 SO 4 , p-toluene sulfonic acid, PMo, or SiW on glycerol ketalization with different ketones (e.g., propanone, butanone, cyclopentanone, and cyclohexanone) at room temperature and in the absence of an auxiliary solvent. The HPW sample exhibited the highest activity among the Brønsted acid catalysts and exhibited high (> 85%) selectivity toward five-membered (solketal) cyclic ketals.…”
Section: Catalytic Acetalization Of Glycerolmentioning
confidence: 99%
“…Under these conditions, it was found that PW was the most active catalyst, achieving a solketal selectivity of 97% at a conversion of 90%. Other ketal derivatives were prepared by using cyclic and acyclic ketones 266 . Supported heteropolyacids have been used as catalysts for this transformation.…”
Section: Solketal Productionmentioning
confidence: 99%
“…They need to work at approximately 70 °C for a long reaction time. Heteropoly acid H 3 PW 12 O 40 (HPW) was used for solketal synthesis at room temperature, but H 3 PW 12 O 40 is a homogeneous catalyst that is difficult to recycle . The heteropoly acid salt Cs2.5 is water tolerant, possesses an acid strength comparable to that of H 3 PW 12 O 40 and has a high surface area .…”
Section: Introductionmentioning
confidence: 99%
“…Heteropoly acid H 3 PW 12 O 40 (HPW) was used for solketals ynthesis at room temperature, but H 3 PW 12 O 40 is ah omogeneous catalystt hat is difficultt or ecycle. [10] Theh eteropoly acid salt Cs2.5 is water tolerant, possesses an acid strength comparable to that of H 3 PW 12 O 40 and has ah igh surface area. [19] This materiali sa lso interesting to explore as ac atalyst for glycerol acetalization with acetone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation